2014
DOI: 10.1016/j.tranon.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood for Epidermal Growth Factor Receptor Mutation Detection in Non-Small Cell Lung Cancer Patients

Abstract: OBJECTIVE: It is important to analyze and track Epidermal Growth Factor Receptor (EGFR) mutation status for predicting efficacy and monitoring resistance throughout EGFR-tyrosine kinase inhibitors (TKIs) treatment in non-small cell lung cancer (NSCLC) patients. The objective of this study was to determine the feasibility and predictive utility of EGFR mutation detection in peripheral blood. METHODS: Plasma, serum and tumor tissue samples from 164 NSCLC patients were assessed for EGFR mutations using Amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 43 publications
6
54
1
Order By: Relevance
“…1). In the study reported by Li and colleagues (49), EGFR mutation was detected in both plasma and serum, and the data of plasma and serum were analyzed as two independently studies. Thus, 27 eligible studies were included in meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…1). In the study reported by Li and colleagues (49), EGFR mutation was detected in both plasma and serum, and the data of plasma and serum were analyzed as two independently studies. Thus, 27 eligible studies were included in meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…30 articles were reviewed in detail after the article titles and abstracts were checked [9, 16, 1946]. Eight studies were excluded from the meta-analysis [3946], leaving 22 studies that fulfilled the eligibility criteria [9, 16, 1938] (Table 1). Among the 8 excluded studies, 7 did not provide sufficient data for extracting odds ratio (OR) or hazard ratio (HR) [3945], and other 1 study was excluded because the same cohort of patients was used in other selected study [46].…”
Section: Resultsmentioning
confidence: 99%
“…4 studies reported the prognostic role of KRAS genotype detected in cfDNA for NSCLC [20, 23, 25, 34]]. Another 7 studies dealt with the predictive role of EGFR genotype presented in cfDNA for NSCLC patients who were treated with tyrosine kinase inhibitors of EGFR (EGFR-TKIs) [16, 24, 26, 3538]. …”
Section: Resultsmentioning
confidence: 99%
“…Li et al [30] found that EGFR-TKI treatment of tumor-tissue EGFR M+ patients prolonged the PFS of plasma EGFR M- patients compared with plasma EGFR M+ patients, though the result was not statistically significant (19.7 months vs. 11.0 months, P = 0.102). Furthermore, Lam et al [31] found that both the PFS and the OS of plasma EGFR M+ patients were shorter than those of plasma EGFR M- patients.…”
Section: Discussionmentioning
confidence: 99%